Factors That Influence Tax Planning - Rabbani, Randini Raya; Hotang, Keri Boru; Faisal, Yusuf (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2025)
Purpose – This study aims to analyze the influence of Profitability, Leverage, Firm Size, and Transfer Pricing on Tax Planning. Design/methodology/approach – This study uses quantitative research. The population used in this study was companies from the industrial sector listed on the Indonesia Stock Exchange (IDX) for the period 2018-2024. The data collection technique used in this study was a purposive sampling method, selecting 13 companies from a population of 67 companies. The analysis method used was multiple linear regression using E-Views9 software Findings – The result of this study indicate that Profitability has a significant effect on Tax Planning, Leverage does not have a significant effect on Tax Planning, Firm Size does not have a significant effect on Tax Planning, and Transfer Pricing has a significant effect on Tax Planning. This study focuses on the industrial sector. Research limitations/implications – To maintain focus on the initial objectives of this study and considering time constraints, this study limits the discussion of the problem by establishing the following qualifications: The data analyzed are financial reports from industrial sector companies listed on the Indonesia Stock Exchange during the period 2018-2024. In this study, the researcher will only analyze the Effect of Profitability, Leverage, Firm Size, and Transfer Pricing on Tax Planning.